Before the next attack : preserving civil liberties in an age of terrorism - Ackerman, Bruce A. (Yale University Press, 2006)
Terrorist attacks regularly trigger the enactment of repressive laws, setting in motion a vicious cycle that threatens to devastate civil liberties over the twenty-first century. In this book, Bruce Ackerman peers into the future and presents a practical alternative. He proposes an ʺemergency constitutionʺ that enables government to take extraordinary actions to prevent a second strike in the short run while prohibiting permanent measures that destroy our freedom over the longer run. Ackermanʼs ʺemergency constitutionʺ exposes the dangers lurking behind the popular notion that we are fighting a ʺwarʺ on terror. He criticizes court opinions that have adopted the war framework, showing how they uncritically accept extreme presidential claims to sweeping powers. Instead of expanding the authority of the commander in chief, the courts should encourage new forms of checks and balances that allow for decisive, but carefully controlled, presidential action during emergencies. In making his case, Ackerman explores emergency provisions in constitutions of nations ranging from France to South Africa, borrowing some useful aspects and adapting others. He shows that no country today is well equipped to both fend off terrorists and preserve fundamental liberties, drawing particular attention to recent British reactions to terrorist attacks: Book jacket.